2022
DOI: 10.1101/2022.01.23.22269718
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Values and preferences of the general population in Indonesia in relation to COVID-19 self-testing: A cross-sectional survey

Abstract: Objectives: Innovative diagnostics are essential to assist members of the general population become active agents of case detection. In Indonesia, a country with an over-burdened healthcare system, individuals could use self-tests for SARS-CoV-2 to determine their COVID-19 status. To assess the acceptability of SARS-CoV-2 self-testing among the general population in Indonesia, a cross-sectional, population-based survey was conducted in mid-2021 in Jakarta and the provinces of Banten and North Sulawesi. Method… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 17 publications
4
9
2
Order By: Relevance
“…Of the self-testing acceptability studies that have been conducted, our survey findings are aligned with the results of studies conducted in Germany [9], Indonesia [26], Nigeria [27], Kenya [28], the United Kingdom [33], and Greece [34,35] and Cyprus [34], where the study populations also manifested a willingness to use selftesting. Of these studies, only the inquiries in Indonesia [26], Kenya [28], Greece [34,35] and Cyprus [34] targeted the general public. Comparing our survey with that of Goggolidou et al [34] and Mouliou et at.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Of the self-testing acceptability studies that have been conducted, our survey findings are aligned with the results of studies conducted in Germany [9], Indonesia [26], Nigeria [27], Kenya [28], the United Kingdom [33], and Greece [34,35] and Cyprus [34], where the study populations also manifested a willingness to use selftesting. Of these studies, only the inquiries in Indonesia [26], Kenya [28], Greece [34,35] and Cyprus [34] targeted the general public. Comparing our survey with that of Goggolidou et al [34] and Mouliou et at.…”
Section: Discussionsupporting
confidence: 82%
“…In our inquiry, acceptability was conceptualized as a composite of the public’s values toward self-testing, including agreement with the concept of self-testing (73.91% and 60.09% of female and male respondents were in agreement, respectively); willingness to pay for self-testing (if available at an average price of 5.64 USD (SD 4.73) for the 69% of respondents who would pay for a self-test device); willingness to serially self-test (44.57% of females and 39.48% of males expressed willingness to perform weekly self-tests); and likelihood to use self-testing (12.95% and 36.21% of respondents were “very likely” or “likely”, respectively, to use a self-test). Although satisfactory, the rates of likelihood to use a self-test were not as high as those found in Indonesia [ 26 ], Nigeria [ 27 ], or Kenya [ 28 ], other countries where surveys of people’s values and attitudes towards self-testing were conducted in 2021 using the same methodology we used in São Paulo.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In this context, our study shows that self-testing, if endorsed by health authorities and distributed alongside awarenessraising and pre-and post-test counseling, could represent an easy to use, private, and convenient solution that would be bene cial in identifying asymptomatic carriers, initiating earlier isolation and contact tracing, and, ultimately, decreasing the transmission rates of SARS-CoV-2 in Indonesia. This is in line with ndings from a cross sectional survey in Indonesia which found that 62.7% of people agreed with the concept of people being able to self-test for COVID-19 [13].…”
Section: Discussionsupporting
confidence: 89%